Old habits die hard: The need for feminist rethinking in global food and agricultural policies - Andrea M. Collins (Canadian Food Studies, 2018)
A number of global initiatives designed in recent years address global food security and aim to reduce the vulnerability of small-scale and peasant farmers in the face of expanded transnational investment in large-scale agriculture and land acquisition. While there have been efforts to consider women within such initiatives, global governance institutions often overlook the complex gendered dimensions of food systems alongside agricultural land and labour markets. Although institutions emphasize the need for “women’s empowerment”, few policy recommendations have considered its practical application. Indeed, many governance initiatives that address food security or promote land security tend to depoliticize inequalities, which shows the importance of feminist food studies from the perspective of global food and land policy. Integrating a feminist food studies lens to the global governance of food and agriculture allows us to explore the complexities of gendered relations in agricultural practices. A more complete understanding of everyday material, socio-cultural and corporeal experiences within agricultural practices provides a greater understanding of the mechanisms by which gender relations structure food production, land ownership, resource access and governance processes. By using a feminist food studies lens we see a more complete picture of the realities of local resource management and the potential implications for global policymakers such as the World Bank, the Food and Agriculture Organization of the United Nations (FAO) and the United Nations Committee for World Food Security (CFS). Through this framework, I illustrate how feminist analyses challenge conventional approaches to gender in global policymaking related to food and agricultural production.